2021
DOI: 10.1111/ocr.12465
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of three composite materials in bonding attachments for clear aligners

Abstract: Objective The aim of this study was to assess the operation time, shear bond strength, placement accuracy and wear resistance of 3 composite materials (Filtek Z350XT, Filtek Z350XT Flowable and SonicFill) that were used to make attachments for clear aligners. Settings and sample population Laboratory of Stomatology of Shanghai Ninth People’s Hospital affiliated to Shanghai Jiao Tong University School of Medicine. A total of 129 human mandibular premolars were collected, 69 of which were assigned to 3 groups (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 27 publications
6
26
0
Order By: Relevance
“…Results showed that Filtek Z350 had higher SBS value than Filtek Z350 supreme Ultra flowable. This result is similar to the findings reported by Chen et al who evaluated the effect of the same composite types on the SBS of extracted premolars and found that the flowable composite showed lower bond strength (15.3 +/− 2.33 MPa) compared to the conventional Filtek Z350 (20.53 +/− 2.59 MpPa) [2]. It is likely that the amount of inorganic fillers played a major role in these results.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Results showed that Filtek Z350 had higher SBS value than Filtek Z350 supreme Ultra flowable. This result is similar to the findings reported by Chen et al who evaluated the effect of the same composite types on the SBS of extracted premolars and found that the flowable composite showed lower bond strength (15.3 +/− 2.33 MPa) compared to the conventional Filtek Z350 (20.53 +/− 2.59 MpPa) [2]. It is likely that the amount of inorganic fillers played a major role in these results.…”
Section: Discussionsupporting
confidence: 90%
“…For bonding attachments to natural teeth, Chen et al in 2020 found that the highest SBS was gained by bonding attachments with SonicFill composite (23.49 MPa). Filtek Z350XT had an SBS of 20.53 MPa while bonding with Filtek Z350XT Flowable resulted in 20.53 MPa [2]. The AFM images support these results since air abrasion and HFA had a rougher surface than PhA specimens.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations